Using a resident-led patient safety quality council to educate future QI leaders - Goolsarran, Nirvani (Med Educ Online, 2020)
Resident-led councils represent an important initiative to involve trainees in patient safety, but little is known about how to create and sustain one of these councils. We evaluated the impact of a resident-led patient safety council in an internal medicine residency program. We assessed change in resident perception of safety issues over 3 years, scholarship activities, and behavioral choices to participate or lead patient safety activities after residency. The Stony Brook Internal Medicine Residency Program formed the Patient Safety and Quality Council (PSQC) in 2014, consisting of fifteen peer-nominated residents serving a three-year term. Surveys were distributed annually from 2014 to 2017 to measure resident council members’ perception of patient safety. The number of safety-related abstract/publications were tracked during and one year after graduation. Additionally, graduates from the council were surveyed to assess the influence of the council on post residency involvement and leadership in safety activities. A total of 18 residents have participated in the council from 2014 to 2017. Overall, resident perception of safety culture improved. A total of 17/18 (94%) PSQC resident members demonstrated scholarship activities in safety during residency: 8/18 (44%) were engaged in an independent Quality Improvement (QI) project, 5/18 (27%) achieved a quality improvement leadership role post residency. A total of 15 of 18 (83%) recent graduates suggest that involvement with the safety council during residency fostered future involvement in patient safety. Implementation of a resident-led safety council can help to improve the safety culture, generate scholarly activities, and encourage continued participation in patient safety after graduation.